PERLINDUNGAN HUKUM TERHADAP DEBITUR PADA LAYANAN PINJAMAN UANG BERBASIS FINANSIAL TEKNOLOGI DALAM PERSPEKTIF HUKUM PERDATA - Paturochman, Iwan Ridwan; Hayati, Jurni; Sani, Ageng Asmara (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
This research is motivated by the existence of problems in society that are difficult to solve. On the one hand, the community's economic downturn has resulted in them looking at other types of illegal loans. On the other hand, fintech actors take advantage of the situation and conditions of society so that they are trapped by debts and receivables with abnormal interest. Collection methods that are beyond humane limits are disturbing the people who use these loans. Therefore, the author must carry out further studies regarding legal protection for debtors who use illegal online money lending services. The aim of this research is to analyze and examine legal protection for debtors in illegal online money lending services. To analyze and study the legal settlement process undertaken by debtors in Illegal Online money lending services. The method used is normative juridical. The normative juridical approach method is a legal research technique that involves examining library materials (secondary data) using a statutory approach, namely an approach that uses statutory regulations which are useful as a research medium. Apart from that, it uses a conceptual approach, which requires legal concepts as a starting point for research into current legal problems.